2021
DOI: 10.3389/fonc.2021.717180
|View full text |Cite
|
Sign up to set email alerts
|

Radioactive Iodine-125 in Tumor Therapy: Advances and Future Directions

Abstract: Radioactive iodine-125 (I-125) is the most widely used radioactive sealed source for interstitial permanent brachytherapy (BT). BT has the exceptional ability to deliver extremely high doses that external beam radiotherapy (EBRT) could never achieve within treated lesions, with the added benefit that doses drop off rapidly outside the target lesion by minimizing the exposure of uninvolved surrounding normal tissue. Spurred by multiple biological and technological advances, BT application has experienced substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 181 publications
(211 reference statements)
0
17
0
Order By: Relevance
“…The introduction of an image navigation system provides better accuracy and feasibility, which tracks the needle position in real-time by a tracer to locate the lesion on the fusion image, guiding the puncture procedure. In numerous studies, it has been used for the treatment of solid tumors using seed implantation, with a great puncture accuracy [ 70 , 71 ]. Moreover, Ji et al [ 72 ] suggested that there was no significant difference in dosimetric parameters between post-operative and preoperative plans, regardless of the type of organ, including head and neck, chest wall, and abdominopelvic lesions.…”
Section: Prospectsmentioning
confidence: 99%
“…The introduction of an image navigation system provides better accuracy and feasibility, which tracks the needle position in real-time by a tracer to locate the lesion on the fusion image, guiding the puncture procedure. In numerous studies, it has been used for the treatment of solid tumors using seed implantation, with a great puncture accuracy [ 70 , 71 ]. Moreover, Ji et al [ 72 ] suggested that there was no significant difference in dosimetric parameters between post-operative and preoperative plans, regardless of the type of organ, including head and neck, chest wall, and abdominopelvic lesions.…”
Section: Prospectsmentioning
confidence: 99%
“…Along with the development of interventional therapy, computed tomography (CT)-guided iodine-125 ( 125 I) seeds insertion (ISI) and trans-arterial chemical infusion (TAI) have been widely used for advanced non-smallcell LC (NSCLC) [4][5][6][7][8][9][10]. The advantages of interventional therapies include mini-invasive nature and lower treat-ment-related toxicity.…”
Section: Purposementioning
confidence: 99%
“…In this technique, a radioactive source with a short range and strong penetrating power is applied in contrast to conventional radiation therapy. Therefore, once implanted into target area, it provides an uninterrupted and stable short-range irradiation, with lesser damage to surrounding normal tissues [ 11 ]. This technique is easy to operate, and provides effective radio-protection, because its’ energy decays with distance [ 12 ].…”
Section: Purposementioning
confidence: 99%